Pengaruh Penambahan Air Kelapa sebagai Nutrisi Tambahan dalam Budidaya Jamur Tiram Putih (Pleurotus Oustreatus) - Nahda, Afiah Tul; Lahming, Lahming; Rahmah, Nur (Jurnal Pendidikan Teknologi Pertanian, 2025)
White oyster mushrooms are a type of woody mushroom that taste delicious and are nutritious so they are very popular with many people. However, growing oyster mushrooms takes a long time and becomes an obstacle for farmers because they cannot meet market demand. One alternative to increase the production of white oyster mushrooms is by adding nutritional growth regulators in the form of coconut water. This research aims 1). To determine the effect of adding coconut water on the growth of white oyster mushrooms (Pleurotus ostreatus) 2) To determine the effect of differences in coconut water concentration on the growth of oyster mushrooms (Pleurotus ostreatus). This type of research is pseudo-quantitative in the form of experimental research. The method used was a completely randomized design (CRD) with 4 treatments and 3 replications so that there were 12 logs. It was found that there was no real effect of the addition of coconut water and the concentration level given on the pinhead emergence time parameters. Because the results show that the average time for control pinheads to appear is not much different from the time for treated pinheads to appear. In contrast to the parameter for the number of caps, the results showed that the addition of coconut water and the concentration level given had a significant effect on the number of mushroom caps. The provision of coconut water is said to have a real effect because there is a large difference between the average number of control hoods and those given treatment. The most obvious treatment was treatment C with the addition of 400 ml of coconut water